8. REFORMASI BISROKRASI INDONESIA HARAPAN DAN KENYATAAN - Astuti, Retno Sunu (FORUM, 2007)
When President Yudhoyono started his presidential term, there was a great public expectation that there would be betterment in the Indonesian bureaucracy. However, the 2006â€™s PERC survey ranked Indonesian bureaucracy as the second worst in Asia. Among the causes are the incapability of the government to reform its structure, norms, values andÂ  regulation that are still colonial oriented. Among the weaknesses are â€œfatâ€ organization, overlapping institutional authority, unproffesional bureaucracy, mass coruption andÂ  nepotism, un-coordinated and un-integrated programs, as well as low dicipline and working ethos among the bureaucrats. These all resulted in unsatisfactory public service. Reform should be done by all stakeholders. The President shoud makeÂ  a sound grande design, other stakeholder give their support, while the public realize a check and balance system. Efforts in the Presidentâ€™s last two-year end of term should be focused on the reform on the aspects of institutions, government apparatuses, culture, enviroment and leadership.